Recent trends in collaborative learning: a systematic review and analysis - Marreh, Sambujang; Velankar, Yogesh P. (Institute of Advanced Engineering and Science, 2024)
This study analyses the scientific literature publications from 2015 to 2022 on collaborative learning published in the reputable database Scopus. The study uses the recommended preferred reporting items for systematic reviews and meta-analysis (PRISMA) protocol to conduct a systematic analysis of the literature. A total of 664 relevant journal articles were included following the PRISMA framework. The study examined trends in journal article publications, the field of study in which the collaborative learning approach is applied, the participants used as study subjects, and the first authors' country of affiliation. The review highlights a significant growth in the amount of educational research that utilizes collaborative learning approaches. Researchers paid more attention to studies that focused on tertiary education settings, next on elementary school environments and a few studies examined collaborative learning within the context of the workplace. Based on the International Standard Classification of Education (ISCED) fields of study, many of the collaborative learning studies conducted over the recent four years (2019–2022) were aimed at enhancing students’ performance in multidisciplinary settings, followed by computing and physical sciences. The results indicate a considerable rise in technologyenhanced collaborative learning practices.